Rhizobia amylase production using various starchy substances as carbon substrates - Oliveira,Arlem Nascimento de (2007)
Six isolates of indigenous rhizobia of Central Amazonia were screened for the production of amylases in liquid media using various starchy substances as carbon sources. All rhizobia strains could produce more extracellular protein, biomass and amylases with the different kinds of carbon substrates. Among the carbon sources tested maltose was the best substrate for protein and amylase production. In general, peach palm flour and corn starch (maizena®) were also considered to be good carbon sources for rhizobia amylases. On the other hand, the biomass production by the rhizobia isolates was higher in the presence of oat flour. INPA strain R-926 was a good amylase producer in maltose (1.94 U) and corn starch (0.53 U) media. INPA strain R-991 was also a good amylase producer in maltose (1.66 U) and corn starch (1.59 U) yielding significant extracellular amylase. Correlation analysis showed significant and positive relationships between rhizobia amylases and final pH (r = 0.49, P < 0.05), extracellular protein (r = 0.47, P < 0.47) and biomass production (r = 0.69, P < 0.01) in the maltose medium. The results obtained in this study revealed several Central Amazonian rhizobia strains as promising sources of amylase for biotechnological applications, especially in starch industry.